CT characterisation of feline adrenal glands. Issue 4 (April 2020) - Mallol, Claudia; Altuzarra, Raúl; Espada, Yvonne; Tobón Restrepo, Mauricio; Serrano, Emmanuel; Novellas, Rosa
Objectives: The objectives of this study were to describe the CT characteristics of the adrenal glands in healthy cats, to provide normal reference biometry for adrenal gland size and attenuation values, and to investigate the association with age, sex, laterality and body weight. Methods: Retrospective evaluation of 30 CT studies of healthy adult cats recruited from September 2013 to July 2015 was performed. Healthy cats >1 year of age were included based on the absence of clinical signs, unremarkable physical examination, normal results of the complete blood count, biochemical profile, feline immunodeficiency virus, feline leukaemia virus and Bartonella species infection tests. The relationship between gland biometry (size and attenuation values) and the age, sex, laterality and body weight of cats were tested by two-way ANOVA. The intraclass correlation coefficient was assessed and mean, SD, range and reference interval provided. Results: Twenty-seven cats were included. Bilobed, arrowhead and oval adrenal gland shape patterns were recognised, the first being most common. No statistically significant differences were observed between the biometric parameters (length, height and attenuation values) and age, sex, laterality or body weight of the cats. Regarding the width of the adrenal glands, there was a statistically significant effect of sex and laterality. T he length (11.6 ± 2.1 mm) and height (6.1 ± 1.3 mm) were the most consistent biometrical parameters to describe adrenal glands. Conclusions and relevance: Adrenal gland shape, size and attenuation CT data of healthy feline patients are provided in this study, as well as normal reference intervals for morphometric characterisation based on adrenal length and height.